If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+3-5x=4x+3
We move all terms to the left:
9x+3-5x-(4x+3)=0
We add all the numbers together, and all the variables
4x-(4x+3)+3=0
We get rid of parentheses
4x-4x-3+3=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| x^2+8=540 | | -7(z+6)=-56 | | 2^n=8^20 | | 2=m-13 | | 9-3/4(3x-16)=48 | | -8x-8=-4(2-3x) | | (40y+30)=5 | | 25x+30=125 | | 8=b4+ 4 | | 7e+1=3+5 | | –174=3x | | f-13=6 | | 12=-39+3x | | p=-6(8p-8)+p | | 12=6×a | | 10x-10+12x-4+x=180 | | 118+60+x=180 | | 3.1x=380 | | (3x-1)2=(10x-26) | | 6.8-1.3x=0.6x-2.7 | | 0.2g-1.8=-2.6 | | 4w+-3.7=-15.7 | | ∠1=3y-6 | | 0.7(h+9)=0.63 | | -4x(x-2)=(3x-8) | | 1+2b=-11-b | | X+49+x+64+91=180 | | 380=3.1x | | 5.5+2y=-11.5 | | 2-7(2y-6)=6(-7+10) | | -4+7z+3-2z+7=0 | | 3.5h=2.25h |